Polyaromatic Hydrocarbon Degradation and Dioxygenase Gene Detection from Alteromonas alvinellae Bt05 - Ahmad Thontowi; Nanik Rahmani; Yopi Yopi (ANNALES BOGORIENSES, 2013)
Bt05 is marine bacterium which was isolated from the Jakarta Bay, Indonesia. The aim of this study was to characterize PAHs-degrading property, molecular identification by partial analysis of 16S rRNA gene and to partially analyze dioxygenase gene of Bt05 isolate. Our further study on this isolate revealed that it could degrade three PAHs (phenanthrene, dibenzothiophene, fluorene) between 60%–90% within 11 days at 100 ppm level. This finding indicated the potential of the isolate for bioremediation of PAHs. The isolate was identified as Alteromonas alvinellae by phylogenetic analysis of 16S rRNA gene sequence. Sequence analysis of the PCR product of PAH dioxygenase genes amplified using two primer set (iiDA and ppAH) of the isolate were identified 97% as naphthalene dioxygenase gene (phaAc) and 58% as 1,2-dioxygenase.